KONSTITUSI DI ZAMAN DIGITAL: RELEVANSI, ADAPTASI, DAN DAMPAKNYA - Laila Khansa Muzaimah; Aditya Abimanyu (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The development of digital technology has brought about major changes in various aspects of human life, including law and state administration. The constitution, as the highest legal basis, is faced with new challenges in answering issues that arise in the digital world, such as personal data protection, freedom of expression on the internet, and cybercrime. This study uses a literature review method by examining academic articles published in 2018-2025, to analyze the relevance, adaptation, and impact of the constitution in the digital era. The study results show that the constitution still has an important role in regulating and protecting the rights of citizens in the digital world. Still, adjustments to the principles and interpretations of the law are needed to remain effective amidst rapid social and technological changes. Adaptation of the constitution is key to maintaining democracy, protecting human rights, and ensuring the sustainability of legal development in the future.